Development of a Novel Biosensor Using Cationic Antimicrobial Peptide and Nickel Phthalocyanine Ultrathin Films for Electrochemical Detection of Dopamine - Maysa F. Zampa; Inês Maria de S. Araújo; José Ribeiro dos Santos Júnior; Valtencir Zucolotto; José Roberto de S. A. Leite; Carla Eiras (International Journal of Analytical Chemistry)
The antimicrobial peptide dermaseptin 01 (DS 01), from the skin secretion of Phyllomedusa hypochondrialis frogs, was immobilized in nanostructured layered films in conjunction with nickel tetrasulfonated phthalocyanines (NiTsPc), widely used in electronic devices, using layer-by-layer technique. The films were used as a biosensor to detect the presence of dopamine (DA), a neurotransmitter associated with diseases such as Alzheimer's and Parkinson's, with detection limits in the order of 10−6 mol L−1. The use of DS 01 in LbL film generated selectivity in the detection of DA despite the presence of ascorbic acid found in biological fluids. This work is the first to report that the antimicrobial peptide and NiTsPc LbL film exhibits electroanalytical activity to DA oxidation. The selectivity in the detection of DA is a fundamental aspect for the development of electrochemical sensors with potential applications in the biomedical and pharmaceutical industries.